PENGARUH BUDAYA ORGANISASI DAN STRUKTUR ORGANISASI TERHADAP KUALITAS INFORMASI AKUNTANSI DENGAN KUALITAS SISTEM INFORMASI AKUNTANSI SEBAGAI VARIABEL INTERVENING (Studi pada Baitulmaal Wattamwil (BMT) di DKI Jakarta) - Taufik Akbar (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2018)
This study was to investigate the influence of organizational culture and organizational structure of the quality of accounting information with the quality of accounting information systems as an intervening variable. The object of this study is the accounting department at Baitulmaal Wattamwil (BMT) located in Jakarta. This study was conducted on 43 respondents using cross sectional approach. Therefore, the analysis of the data used is SmartPLS. The results showed that the variables of organizational culture affect the quality of accounting information systems, organizational structure affect the quality of accounting information systems, the quality of accounting information systems affect the quality of information accounting. This is evidenced from the results of hypothesis testing as seen from T-Stats (≥1,96). The quality of accounting information system mediates the influence of organizational culture on the quality of accounting information, and the quality of accounting information systems mediating influence between the organizational structure of the quality of accounting information. This is evidenced from Sobel test results were seen from the t-value (≥1,96).